Enhanced Propriety-Based I/Q Imbalance Compensation in LTE/NR Receivers - Paireder, Thomas; Motz, Christian; Huemer, Mario (IEEE transactions on signal processing, 2021)
In mobile communications, radio-frequency receivers are mainly implemented using the direct-conversion architecture. A critical aspect in the design of this receiver type is the matching between the analog in-phase (I) and quadrature (Q) paths. Any gain or phase imbalance generates image components in the baseband, which distort the desired receive signal. Many digital solutions for online compensation of this effect have been proposed in the literature. A common statistical measure that is used by non-data-aided algorithms is the so-called propriety of the receive signal. This concept is suitable for most communication signals, but fails, for instance, in case of the real-valued binary phase-shift keying (BPSK) modulation. In this work, we provide a thorough statistical analysis of Long-Term Evolution (LTE) and New Radio (NR) up- and downlink sequences, which allows us to extend a propriety-based estimator to improper alphabets. This algorithm employs the method of moments. We show that the observed signal statistics can be altered by omitting a predefined set of samples. In a second step, we prove that this concept substantially enhances the imbalance compensation also for proper quadrature amplitude modulation (QAM) alphabets. All theoretical results are supported by simulations to evaluate the actual performance gains in practical scenarios. Depending on the resource block allocation and the noise levels, we obtain double-digit improvements of the image rejection ratio, while reducing the computational effort by about 6.6% compared to the standard moment-based I/Q imbalance estimator.